Salt induced transitions of chromatin core particles studied by tyrosine fluorescence anisotropy. - Libertini, L J (1980)
Chromatin core particles containing 146 base pairs of DNA have been found to undergo a single defined transition below 10 mM ionic strength as studied by both sedimentation velocity and tyrosine fluorescence anisotropy. A method is described for the preparation of such core particles from chicken erythrocytes with greater than 50% yield.